1988
DOI: 10.1002/1097-0142(19880201)61:3<580::aid-cncr2820610326>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Acute leukemia and pregnancy

Abstract: Acute leukemia was diagnosed in five pregnant patients who received chemotherapy during the course of pregnancy. Three were undergoing chemotherapy at conception. One patient died in the fifth month of pregnancy and the anatomic study of the fetus was normal. Four babies had low birth weights at birth. Of the four one was born prematurely, but without malformations. Later development was normal. The results are reviewed and compared with data from the literature, leading to the conclusion that pregnancy is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…However, there is general agreement concerning the initiation of induction therapy in the 2nd-3rd trimesters. Good results are often obtained at a standard or moderately aggressive dose rather than a smaller dose (Bartsch et al 1988;Caligiuri and Mayer 1989;Feliu et al 1988;Gondo et al 1990; Roy et al 1989). In the treatment of pregnant patients with leukemia, a detailed protocol is needed based on the month of pregnancy, avoiding the use of alkylating drugs and antifolic agents and the combination with irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is general agreement concerning the initiation of induction therapy in the 2nd-3rd trimesters. Good results are often obtained at a standard or moderately aggressive dose rather than a smaller dose (Bartsch et al 1988;Caligiuri and Mayer 1989;Feliu et al 1988;Gondo et al 1990; Roy et al 1989). In the treatment of pregnant patients with leukemia, a detailed protocol is needed based on the month of pregnancy, avoiding the use of alkylating drugs and antifolic agents and the combination with irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine exposure after first trimester does not increase the risk of fetal malformations (7)(8)(9)(20)(21)(22)(23) . The risk of fetal malformation associated with chemotherapy during the first trimester is said to be 10-20% (18,19) , whereas later in pregnancy it is reported to be no higher than that of general population (3%) (17)(18)(19)(20)24) . Morishita et al (23) investigated the effects of chemotherapy in the fetus of women treated with multiagent chemotherapy for acute myelogenous leukemia during the third trimester and found that fetal hematopoiesis was not adversely affected and no malformations were observed (23) .…”
Section: Discussionmentioning
confidence: 99%
“…However, great concerns remain about the teratogenic and mutagenic effects of radiation and chemotherapy on the fetus. It is clear from animal models that the first trimester is the time of greatest risk, hence, many authors advice against the use of cytostatic agents during this period (17)(18)(19) . Intrauterine exposure after first trimester does not increase the risk of fetal malformations (7)(8)(9)(20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…Acute leukemia during pregnancy is very rare with an estimated frequency of 1 in 75,000-100,000 [3, 6, 7]. AML accounts for approximately two-thirds of leukemia cases seen during pregnancy and the diagnosis is generally made during the second and third trimesters [3, 5].…”
Section: Casementioning
confidence: 99%